Organizational and Economic Factors of Cotton Growing Development in Uzbekistan - Odiljon Shermatov (International Journal on Integrated Education, 2022)
Using scientific research on the development and economic efficiency of cotton, the main crop in Uzbekistan, the article identifies the factors affecting the economic efficiency of the sector. Prepared conclusions and recommendations for improving cotton's economic efficiency.